Pyroxsulam Resistance in Apera spica-venti: An Emerging Challenge in Crop Protection - Soham Bhattacharya; Madhab Kumar Sen; Katerina Hamouzová; Pavlína Košnarová; Rohit Bharati; Julio Menendez; Josef Soukup (Plants)
Apera spica-venti, a prevalent weed in Czech winter wheat fields, has developed resistance to ALS-inhibiting herbicides due to their frequent use. This study reports a biotype of A. spica-venti resistant to pyroxsulam, with cross and multiple resistance to iodosulfuron, propoxycarbazone, pinoxaden, and chlortoluron. Dose–response experiments revealed high resistance of both R1 and R2 biotypes to pyroxsulam, with resistance factors (RF) of 6.69 and 141.65, respectively. Pre-treatment with malathion reduced RF by 2.40× and 1.25× in R1 and R2, indicating the potential involvement of cytochrome P450 (CytP450). NBD-Cl pre-treatment decreased RF only in R2, suggesting possible GST involvement. Gene analysis revealed no mutations (at previously reported sites) or overexpression in the acetolactate synthase (ALS) gene. However, a significant difference in ALS enzyme activity between resistant and susceptible biotypes points to target-site resistance mechanisms. Studies with 14C-labeled pyroxsulam showed that reduced absorption and translocation were not likely resistance mechanisms. In summary, herbicide resistance in A. spica-venti appears to result from multiple mechanisms. Possible causes include target-site resistance from an unidentified ALS mutation (within coding or regulatory regions). Enhanced herbicide metabolism via CytP450s and GSTs is also a contributing factor. Further experimental validation is needed to confirm these mechanisms and fully understand the resistance. This evolution underscores the adaptive capacity of weed populations under herbicide pressure, emphasizing the need for alternative control strategies.